THE CORRELATION BETWEEN THE INTELLIGENCE LEVEL AND THE ABILITY TO COMPREHEND VISUAL MATERIALS - Faidah Yusuf (UIN Alauddin Makassar, 2013)
AbstractThis research was correlational research. The population consisted of the First Year of Nursing Department at SMK Darussalam Makassar with two classes of Nursing Department as sample. This research employed two kinds of instruments for collecting data. Data on students’ intelligence and their visual material comprehension were analyzed in percentage by using descriptive statistics persons’ product moment correlation and SPSS ver 15.0 for windows to find out whether or not there was correlation between the intelligence level and the ability to comprehend visual materials of SMK Darussalam Makassar. The result of the research showed that there was a significant correlation between the intelligence level and the ability to comprehend visual materials of SMK Darussalam Makassar, as the students categorized into positive category, students comprehension classified into good classification. However, the data shows that the correlation between the intelligence level and the ability to comprehend visual materials exists. It was proved by the result of correlation analysis showing that score of r test was greater than r table value. Therefore, it can be interpreted that the research hypothesis is accepted.AbstractPenelitian ini merupakan penelitian korelasional.Populasi dalam penelitian ini terdiri dari siswa kelas satu Jurusan Keperawatan di SMK Darussalam Makassar.Sampel terdiri dari dua kelas jurusan Keperawatan.Penelitian ini menggunakan dua jenis instrumen untuk mengumpulkan data.Data kecerdasan siswa dan pemahaman materi visual mereka dianalisis dalam persentase dengan menggunakan statistik deskriptif korelasi product moment dan SPSS ver 15.0 for windows untuk mengetahui apakah ada atau tidak hubungan antara Tingkat Kecerdasan dan Kemampuan untuk Memahami Materi Visual SMK Darussalam Makassar. Hasil penelitian menunjukkan bahwa ada hubungan yang signifikan antara Tingkat Kecerdasan dan Kemampuan untuk Memahami Materi Visual siswa SMK Darussalam Makassardikategorikan positif serta pemahaman mereka diklasifikasikan baik. Namun, data menunjukkan bahwa korelasi antara Tingkat Kecerdasan dan Kemampuan untuk Memahami materi Visual ada meskipun posisi moderat.Hal ini terbukti dari hasil analisis korelasi menunjukkan bahwa skor tes-r lebih besar dari nilai tabel-r.Oleh karena itu dapat diartikan bahwa hipotesis penelitian diterima.